Non-phosphorylating glyceraldehyde-3-phosphate dehydrogenase is post-translationally phosphorylated in heterotrophic cells of wheat (Triticum aestivum) - Bustos, Diego Martin (2002)
In wheat, non-phosphorylating, NADP-dependent glyceraldehyde-3-phosphate dehydrogenase (GAPN) was found to be encoded by one gene giving rise to a single protein. However, Western blots revealed two different subunits of about 58 and 60 kDa in endosperm and shoots. The latter was attributed to in vivo phosphorylation of shoot GAPN. No modification occurred in leaves, where the enzyme is composed by a single 58 kDa polypeptide. GAPN partially purified from shoots and endosperm was dephosphorylated in vitro with alkaline phosphatase. Phosphorylated GAPN exhibited similar affinity for substrates but a lower Vmax compared to the non-phosphorylated enzyme. Results suggest that reversible phosphorylation of GAPN could regulate NADPH production in the cytosol of heterotrophic plant cells.